Design and Performance of Composite Cold Thermal Energy Storage Plate in Medical Refrigerators - Chen Junwen; Wang Yu; Cheng Feng (Zhileng xuebao)
To optimize the thermal performance of a medical refrigerator, a composite cold thermal energy storage plate was considered. A design scheme for a composite cold thermal energy storage plate in a medical refrigerator with a uniform and controllable temperature field was proposed. An experimental platform was developed. A medical refrigerator and the composite cold thermal energy storage plate were designed according to the principle of composite cold thermal energy storage. From the perspective of the equal mass scheme and the equal phase-change latent heat scheme, the inner-wall temperature change and cold thermal energy storage time of the phase-change materials (n-tetradecane, CaCl2?6H2O, and water) in the cold thermal energy storage plate were compared. It was found that an equal mass combination of 1.5 kg n-tetradecane in the inner layer and 1.5 kg CaCl2?6H2O in the outer layer of the cold thermal energy storage plate produced the best performance. Further, the cold thermal energy storage duration, average temperature, maximum inhomogeneous coefficient, and the cooling discharge rate of the cold thermal energy storage plate with the best performance at 2–8 ℃ were compared with different positions in the medical refrigerator (horizontally located on both sides, stacked on both sides, diagonally placed, and perimetrically placed). The results indicated that the composite cold thermal energy storage plate placed diagonally had the longest storage duration; the average temperature for the four placement positions was within 2–8 ℃. When the two sides were stacked, the maximum inhomogeneous coefficient was the lowest, and the cold discharge rate of the cold thermal energy storage plate was the highest. Considering temperature uniformity as the priority, the cold thermal energy storage effect of an equal-mass combination scheme stacked on both sides was preferred. The experimental results provide a reference for promoting the application of composite cold thermal energy storage plates for medical refrigerators in cold-chain transportation.